Amorphous Boron Nitride: A Universal, Ultrathin Dielectric For 2D Nanoelectronics. (21st March 2016) - Glavin, Nicholas R.; Muratore, Christopher; Jespersen, Michael L.; Hu, Jianjun; Hagerty, Phillip T.; Hilton, Al M.; Blake, Austin T.; Grabowski, Christopher A.; Durstock, Michael F.; McConney, Michael E.; Hilgefort, Drew M.; Fisher, Timothy S.; et al.
Abstract : Next‐generation nanoelectronics based on 2D materials ideally will require reliable, flexible, transparent, and versatile dielectrics for transistor gate barriers, environmental passivation layers, capacitor spacers, and other device elements. Ultrathin amorphous boron nitride of thicknesses from 2 to 17 nm, described in this work, may offer these attributes, as the material is demonstrated to be universal in structure and stoichiometric chemistry on numerous substrates including flexible polydimethylsiloxane, amorphous silicon dioxide, crystalline Al2 O3, other 2D materials including graphene, 2D MoS2, and conducting metals and metal foils. The versatile, large area pulsed laser deposition growth technique is performed at temperatures less than 200 °C and without modifying processing conditions, allowing for seamless integration into 2D device architectures. A device‐scale dielectric constant of 5.9 ± 0.65 at 1 kHz, breakdown voltage of 9.8 ± 1.0 MV cm −1, and bandgap of 4.5 eV were measured for various thicknesses of the ultrathin a ‐BN material, representing values higher than previously reported chemical vapor deposited h ‐BN and nearing single crystal h ‐BN. Abstract : Ultrathin amorphous boron nitride films of thicknesses as low as 2 nm are deposited by low temperature pulsed laser deposition. Wafer‐scale process scalability with growth temperatures below 200 °C, film structure and chemistry invariance for numerous prospective substrates, and exceptional dielectric performance open up exciting possibilities to integrate a ‐BN films in next‐generation 2D nanoelectronic material constructs.